Analisis Kasus Sengketa Merek Pada Perusahaan Prada S.A Dengan PT Manggala Putra Perkasa Di Tinjau Dalam Hukum Perdata - Yarulfadillah, Hanyf Ruqo; Ansari, Teuku Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
A brand is a sign which can be in the form of an image, name, word, letter, number, color arrangement, or a combination of these elements which has the function of distinguishing goods and services in trading activities. A trademark is a type of brand that is used to differentiate products traded by a person, several people together, or a legal entity from other similar products. Problems related to Intellectual Property Rights, especially in terms of brands, are problems that continue to grow along with developments in science and the world of commerce. This can be seen from the increase in brand infringement cases that are currently occurring. One related case is Prada S.A Italy's lawsuit against PT. Manggala Putra Perkasa, where the court decided in Judicial Review No.274 PK/Pdt/2003 that the brand was the legal property of Prada S.A., as stated in Judicial Review Decision No.274 PK/Pdt/2003. Methods used in the research This is an analytical description method with a normative juridical approach. Legal research is a process of discovering legal rules, principles and legal doctrines in order to answer the issues faced and using secondary research data, which includes official documents, books, journals and research results in the form of reports.